Efektivitas Komunikasi Elektronik Word Of Mouth Terhadap Produk Jilbab - Amaliah Amaliah; Saladin Ghalib; Maryono Maryono (Universitas Lambung Mangkurat, 2018)
This study aims to look at the extent to which electronic communication effectiveness of word of mouth to veiling product by community members using the theory Lavidge and Stainer as a benchmark for each response given in response stairs. Used stair response is the awareness, knowledge, liking, preferences, and purchase convoction. Which then each household's response summed up into the effectiveness of e wom on each response to occur on product purchasing decisions.The research method used descriptive qualitative research, by conducting structured interviews and comparing the results with previous studies and existing theories.In response awareness, there are 91.30%, 82.6% knowladge, liking 95.65%, 82.6% preferences, convictiong 78.26%, 82.6% purchase, it can be concluded ewom effectiveness at each stage of the response received positive results presentation. Keywords: Communications, E Wom, Purchase Decision